พฤติกรรมการเปิดรับข่าวสาร กับความรู้ ทัศนคติ และการมีส่วนร่วมส่งเสริมการปกครองระบอบประชาธิปไตย ของเยาวชนทั้งในระบบ/นอกระบบการศึกษา - อัจฉรามณี สามิภักดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 1996)
Investigates the correlation of media exposure, knowledge, attitude and participation in democracy promotion among high school students under the departments of general education and non-formal education. Questionnaires were used to collect the data from a total of 400 samples. Frequency, percentage, mean, t-test and Pearson s Product Moment Correlation Coefficient were employed for the analysis of data. SPSS program was used for data processing. The results of the study are as follows: 1. Exposure to information regarding democracy, knowledge and attitude between high school students under general education department and under non-formal education department are different. But their participation in democracy promotion are not different. 2. Exposure to information regarding democracy from radio and printed media high school students is not correlated with their knowledge in democracy . But Exposure to information regarding democracy promotion from television is significantly correlated with their knowledge in democracy. 3. Exposure to information regarding democracy among high school students is not correlated with attitude toward democracy. 4. Exposure to information regarding democracy among high school students is correlated with participation in democracy promotion.